Exploring Physiological Linkage in Same-Sex Male Couples - Li, Xiaomin; Kuelz, Ashley; Boyd, Savannah; August, Kristin; Markey, Charlotte; Butler, Emily (Frontiers in Psychology, 2021)
We explore physiological linkage (i.e., covariation of physiological channels between interacting partners; PL) among 34 same-sex male couples. Interbeat interval, an indicator of cardiovascular arousal, was collected across four conversational contexts in the lab: 1) a baseline period that did not involve conversation, 2) a conversation about body image, 3) a conversation about health goals, and 4) a recovery period that allowed for unstructured conversation. We used a newly developed R statistical package (i.e., rties; Butler & Barnard, 2019) that simplifies the use of dynamic models for investigating interpersonal emotional processes. We identified two different PL patterns: 1) a simple one that was characterized by stable synchronization and low frequency of oscillation; and 2) a complex one that was characterized by drifting synchronization, high frequency of oscillation, and eventual damping. Guided by social baseline theory and the reactive flexibility perspective, we explored the interactions between couple relationship functioning (i.e., love, conflict, commitment, sexual satisfaction, and relationship length) and conversational context as predictors of the PL patterns. The results suggest that partners in well-functioning relationships and emotionally challenging situations may be especially likely to show complex PL patterns that may reflect (or support) coregulatory processes.